Theological Review of the Meaning of Returning Tithe Offerings to God's Treasury According to Malaki 3:10: A Study in the Seventh-day Adventist Church (GMAHK) Environment - Jimmy Allen Sakul; Janes Sinaga; Juita Lusiana Sinambela (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The purpose of this research is to provide a correct understanding of tithing to the treasury house, examine the types of tithe offerings in the Bible, who has the right to manage and use the tithe offering and to increase the loyalty of Seventh-day Adventist Church members in giving tithe offerings. This research method uses qualitative methods with literature review. Offerings and tithes are not something foreign, they are even an integral part of the worship of God's people. But in practice there are still many God's people, especially among Seventh-day Adventists, this is because they still don't understand the meaning of the verse in Malaki 3:10. A tithe offering should be brought into God's treasury house (church), but there are some members of the Seventh-day Adventist Church who do not follow the standard of faith, but they use or manage it themselves according to their own understanding.